“I Had Changed My Name … To Break With The Past”: Identity Crisis Of African Americans In Maurice C. Ruffin’s Novel Entitled We Cast A Shadow (2019) - Marlina, Leni; Handayani, Rika; Wahyuni, Delvi; Ritma, Ritma (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This study explores identity crisis in Maurice Carlos Ruffin's We Cast A Shadow (2019), focusing on African Americans' struggles for societal acceptance and personal fulfillment. Anchored in Franz Fanon's postcolonial theory (2008), the analysis examines the protagonist's negotiation of identity against a backdrop of historical oppression and systemic racism. The study employs a detailed literary analysis of the novel's prose to reveal how the protagonist's journey from childhood adversity to adulthood reflects a broader quest for self-actualization amid prejudice and inequality. Central to this exploration is the protagonist's aspiration to transcend their Blackness and assimilate into the dominant White American paradigm, highlighting the impact of internalized racism and societal pressures. The narrative poignantly depicts the erosion of the protagonist's agency as they resort to drastic measures to conform to an idealized standard of beauty and acceptance. This transformation into a semblance of Whiteness serves as a powerful allegory for the existential struggles of marginalized individuals navigating identity politics. Through a nuanced analysis of textual motifs and character dynamics, this study underscores the ongoing relevance of identity crises in contemporary discourse and emphasizes the need for societal introspection and transformation toward racial equity and inclusion. Abstrak Studi ini mengeksplorasi krisis identitas dalam novel We Cast A Shadow (2019) karya Maurice Carlos Ruffin, dengan fokus pada perjuangan orang Afrika-Amerika untuk diterima oleh masyarakat dan memenuhi kebutuhan pribadi. Berdasarkan teori postkolonial Franz Fanon (2008), analisis ini meneliti negosiasi identitas protagonis dalam konteks penindasan sejarah dan rasisme sistemik. Studi ini menggunakan analisis sastra yang mendetail dari prosa novel untuk mengungkap bagaimana perjalanan protagonis dari masa kanak-kanak yang penuh kesulitan hingga dewasa mencerminkan pencarian jati diri yang lebih luas di tengah prasangka dan ketidakadilan. Pusat dari eksplorasi ini adalah aspirasi protagonis untuk melampaui kulit hitam mereka dan berasimilasi ke dalam paradigma Dominan Kulit Putih Amerika, menyoroti dampak rasisme internal dan tekanan masyarakat. Narasi ini secara menyentuh menggambarkan pengikisan agensi protagonis ketika mereka resorting pada langkah drastis untuk menyesuaikan diri dengan standar kecantikan dan penerimaan ideal. Transformasi ini menjadi kesamaan dengan kulit Putih berfungsi sebagai alegori yang kuat untuk perjuangan eksistensial individu terpinggirkan dalam politik identitas. Melalui analisis mendalam terhadap motif tekstual dan dinamika karakter, studi ini menekankan relevansi berkelanjutan dari krisis identitas dalam wacana kontemporer dan menekankan perlunya introspeksi masyarakat dan transformasi menuju kesetaraan dan inklusi rasial. Kata Kunci: Identitas Afrika-Amerika, Krisis Identitas, Pascakolonial.